English Language Teaching through Communicative Method: A Qualitative Study of Pre-service Teachers' Perceptions - Bernardus Kopong Danibao; Maria Jacolina Amping Radja Tari (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study aims to explore pre-service English teachers' perceptions of implementing the Communicative Language Teaching Method (CLT) after being exposed to theoretical and practical pedagogical aspects of CLT through the Teaching English as a Foreign Language Methodology (TEFL 1) course. Method: The present study was a qualitative research as it employed an online survey following the participants' teaching demonstration and reflections as instruments to collect the data. The sample group in the study consisted of 30 EFL male and female pre-service English teachers studying at a private university in a remote area in West Timor-Indonesia. Results: The results indicated that although most participants were highly optimistic about using communicative language teaching methods, they suggested several challenging factors and solutions to promote students' active interaction in CLT classrooms. Novelty: This study attempted to make the TEFL 1 course more relevant for pre-service teachers and promote CLT enactment in English teaching. Ultimately, it is expected that such initiatives encourage pre-service English teachers to implement interactive teaching methods in their future teaching professions.